Using Story Telling for Teaching Language Skills to Intermediate Level Students - Shierly Novita Yappi; Dina Astriana (JournEEL, 2019)
Storytelling is a compelling tool for students to learn English through stories. Encouraging students to read or listen to stories sould therefore help them to learn a second language in a way that is not only fun, but memorable.Learners of English should practice and improve their skills in Reading, listening, writing, and speaking. Some materials may promote the completeness of learning this second language acquisition. However, using storytelling for intermediate level students is a creative way to have the students reinforce more on listening the story, re-writing the script, comprehending the chronological order, and speaking the opinion on the content. In addition, telling a folklore or fairytale is interesting and easy to comprehend. These student’s presentation show how they can manage the body movement, facial expression, and inflexion for making the story understandable by the listeners. The activities may be varied for individual or group based on the situation of the classroom teaching and learning. Thus, the teacher should guide them with detail instruction, as consequence, the students know what to do and what to learn. This technique is known as learning by doing in which learners gradually improve the fluency of speaking, the reading comprehension, and writing performance. Furthermore, the analysis shows how the effects of using storytelling enhance the areas of students’ weaknesses in English to be their strengths.